2017
DOI: 10.1016/j.enconman.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Battery sizing and rule-based operation of grid-connected photovoltaic-battery system: A case study in Sweden

Abstract: The optimal components design for grid-connected photovoltaic-battery systems should be determined with consideration of system operation. This study proposes a method to simultaneously optimize the battery capacity and rule-based operation strategy. The investigated photovoltaic-battery system is modeled using single diode photovoltaic model and Improved Shepherd battery model. Three rule-based operation strategiesincluding the conventional operation strategy, the dynamic price load shifting strategy, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(56 citation statements)
references
References 48 publications
0
54
0
2
Order By: Relevance
“…While much literature exists on the use of grid-connected domestic PV-battery systems for increasing energy self-sufficiency and reducing electricity bills [6][7][8][9][10][11][12][13], literature that examines environmental impacts shows that such systems cannot always be assumed to be 'green'. Kabakian et al (2015) [14] showed that a 1.8 kW PV system with lead-acid batteries in Lebanon had slightly more embodied lifetime greenhouse gas (GHG) emissions than the 1.8 kW PV alone, 92 g of CO 2 -equivalent per kWh delivered compared to 89 g/kWh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much literature exists on the use of grid-connected domestic PV-battery systems for increasing energy self-sufficiency and reducing electricity bills [6][7][8][9][10][11][12][13], literature that examines environmental impacts shows that such systems cannot always be assumed to be 'green'. Kabakian et al (2015) [14] showed that a 1.8 kW PV system with lead-acid batteries in Lebanon had slightly more embodied lifetime greenhouse gas (GHG) emissions than the 1.8 kW PV alone, 92 g of CO 2 -equivalent per kWh delivered compared to 89 g/kWh.…”
Section: Introductionmentioning
confidence: 99%
“…As such, environmental impacts were negative when those operating strategies were applied to Portugal and Poland [18]. The literature is abundant with algorithms for peak reduction, cost minimization and self-sufficiency maximization [6][7][8][9][10][11][12][13]. There is good reason for this: All these objectives are quantifiable and desired by consumers, distribution network operators, or other relevant stakeholders.…”
mentioning
confidence: 99%
“…A possible solution to compensate for the intermittency is to incorporate energy storage unit (ESU) into the PV grid‐connected charging system (simply known as a PV‐ESU grid system) . In this case, the optimum sizes of the alternative sources (PV array and ESU) must be determined to avoid the economic losses to the system while providing the required charging services …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In this case, the optimum sizes of the alternative sources (PV array and ESU) must be determined to avoid the economic losses to the system while providing the required charging services. 19,20 Since the PV-ESU grid charging concept is relatively new, there are limited literature that discuss the component (PV and ESU) sizing and its effects on the utility grid and EV users. 21 Majority of the present and past works deal with the grid charging only.…”
mentioning
confidence: 99%
“…Ru et al [9] and Khalilpour et al [10] addressed the sizing problem with consideration of the operation strategies. Zhang et al summarized the existing methods and proposed an approach, which simultaneously obtained the storage capacity and rulebased operation strategies [11].…”
Section: Introductionmentioning
confidence: 99%